Perlindungan Preventif Ondel-Ondel Sebagai Ikon Budaya Betawi - Najmi Ismail; Puguh Aji Hari Setiawan; Hartana Hartana (RIO LAW JURNAL, 2023)
Indonesia is a developing country which is very rich in Traditional Cultural Expressions which can be considered as a very valuable asset. One of the traditional cultural expressions in Indonesia comes from the DKI Jakarta province, namely Ondel-Ondel. The study was conducted to look at preventive protection efforts carried out by the Provincial Government of DKI Jakarta to protect Ondel-Ondel as Traditional Cultural Expressions and also Betawi Cultural Icons as the state's responsibility as the holder of the Copyright for Traditional Cultural Expressions which is mandated by Law Number 28 of 2014 about Copyright. This study uses a normative juridical approach with descriptive analytical research specifications. The data collection technique used was in the form of a literature study to obtain materials or secondary data in the form of primary legal materials and secondary legal materials which were analyzed qualitatively. Based on the results of the research, it was concluded that the DKI Jakarta Culture Office in carrying out preventive protection of Ondel-Ondel by taking inventory of Ondel-Ondel as Copyrights for Traditional Cultural Expressions and Intangible Cultural Heritage and coaching Ondel-Ondel perpetrators by conducting workshops and Ondel-Ondel performances in the public.